PENETAPAN KADAR FENOLIK TOTAL DARI EKSTRAK ETANOL BUNGA ROSELLA BERWARNA MERAH (Hibiscus sabdariffa L.) DENGAN MENGGUNAKAN SPEKTROFOTOMETRI UV-Vis - Sulastri Sam; Abd. Malik; Selpida Handayani (Jurnal Fitofarmaka Indonesia, 2016)
Essential ingredients comfounds in roselle (Hibiscus sabdariffa L.) petals is anthocyanin pigments which include flavonoid that acts as an antioxidant. The aim of this research is to determine content of total phenolic of red roselle flowers (Hibiscus sabdariffa L.) ethanol extract. Sample as many one kilograms extracted by maceration method using ethanol 96%. Resulty 127,03 grams extract. Total phenolic content determined by UV-Vis spectrophotometer at wavelenght 737 nm with gallic acid equivalent as standard reference with Folin-Ciocalteau reagent. The result show the rendamen of ethanolic extract is 12.703% with total phenolic content is 0.1853%.